POTENSI EKSTRAK ETANOL KULIT BATANG TUMBUHAN MANGROVE (AVICENNIA SPP.) DALAM MENGHAMBAT PERTUMBUHAN BAKTERI AEROMONAS HYDROPHYLA. - Darminto, .; Alimuddin, Ali; Iwan, Dini (Fakultas MIPA UNM, 2009)
The aim of this research is to show the potential of tree bark of mangrove (Avicennia sp.) plant as antibacterial to against Aeromonas hydrophyla. This bacterium causes fishery cultivation disease e.g. the MAS (Motile Aeromonads Septicemia). Antibacterial activity test was done using paper diffusion and dilution methods. The research result showed that extract of tree bark of mangrove (Avicennia sp.) plant having potency as antibacterial particularly to the A. hydrophyla.